2009
DOI: 10.5507/bp.2009.022
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial Cognitive Task Resolution and Expired Minute Ventilation, Oxygen Consumption, Carbon Dioxide Production and Heart Rate

Abstract: Aims:To assess the impact of cognitive task solving on respiratory and cardiovascular parameters. Methods: The ML870B80 Exercise Physiology System was used to record concurrently with EEG, the cardiorespiratory and metabolic functions of subjects during cognitive activity. The Expired Minute Ventilation (V E ), Oxygen Consumption (V O2 ), Carbon Dioxide Production (V CO2 ) and Average Heart Rate (BPM) were ascertained for four periods: (1) rest or starting period, (2) reference period, (3) cognitive task solvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Much of the literature on the relationships between cognitive demands and metabolic measures of work have been hampered by manipulations that produce rather small changes in performance. [47][48][49] In closing, we have shown that it is possible to characterize the relationships among cognitive demands, neural activity, and energy expended in the context of variations in iron status. Critically, we have shown that two distinct aspects of iron status-as indexed by sFt and Hb-play two distinct roles in these relationships.…”
Section: Discussionmentioning
confidence: 91%
“…Much of the literature on the relationships between cognitive demands and metabolic measures of work have been hampered by manipulations that produce rather small changes in performance. [47][48][49] In closing, we have shown that it is possible to characterize the relationships among cognitive demands, neural activity, and energy expended in the context of variations in iron status. Critically, we have shown that two distinct aspects of iron status-as indexed by sFt and Hb-play two distinct roles in these relationships.…”
Section: Discussionmentioning
confidence: 91%
“…The first and most obvious is that the finding of a positive relationship between metabolic energy expended and GFP needs to be replicated. Of concern here is the fact that we used large variations in workload-much larger than those used in earlier studies of the effect of cognitive workload on metabolic measures (Garde, Laursen, Jørgensen, & Jensen, 2002;Petrek, 2008Petrek, , 2009. It may be that the positive relationship that we obtained is only observable at high levels of demand.…”
Section: Discussionmentioning
confidence: 94%